Pendampingan Belajar Peserta Didik dalam Memahami Materi Grafik Fungsi Kuadrat Berbantuan Geogebra - Ayu, Adibah; Septianti, Kirana; Nasiva, Nur; Amalya, Reski Putri; Sriyanti, A.; Jamaluddin, Wahida (KHIDMAH: Jurnal Pengabdian Masyarakat, 2024)
Learning assistance with the help of Geogebra is a positive step in improving students' understanding of quadratic function graph material. This service activity aims to enable students to learn independently by utilizing Geogebra as a medium and improve students' understanding of quadratic function graphs. The method used is learning assistance with an educational approach in understanding Geogebra-assisted quadratic function material, especially the subtopic of exploring the characteristics of quadratic function graphs. The implementation was carried out offline for 3 hours. The stages of learning assistance go through 7 stages, starting from the planning stage, pre test, demonstration, simulation (post test), documentation, use of Geogebra, and evaluation. The pretest results showed an average of 79 while the students' post test results obtained an average of 85. This learning assistance shows an increase in students' understanding of the concept of quadratic function graphs. As an evaluation, the results of the learning independence questionnaire show 77% of learners have learning initiatives, 75% can diagnose learning needs, 74.55% can set learning targets, 79% believe that learning is a challenge, 68% choose learning resources, 72.44% can determine learning strategies, 75% can evaluate learning outcomes, and 79% have a self-concept. By understanding the level of individual learning independence, the facilitator can adjust the metrics to suit the individual's needs.